Solve for w 4w-2(1-w)=-38

Math
4w-2(1-w)=-38
Simplify 4w-2(1-w).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
4w-2⋅1-2(-w)=-38
Multiply -2 by 1.
4w-2-2(-w)=-38
Multiply -1 by -2.
4w-2+2w=-38
4w-2+2w=-38
Add 4w and 2w.
6w-2=-38
6w-2=-38
Move all terms not containing w to the right side of the equation.
Tap for more steps…
Add 2 to both sides of the equation.
6w=-38+2
Add -38 and 2.
6w=-36
6w=-36
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6w=-36 by 6.
6w6=-366
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6w6=-366
Divide w by 1.
w=-366
w=-366
Divide -36 by 6.
w=-6
w=-6
Solve for w 4w-2(1-w)=-38

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top